The Great Unexpected - Creech, Sharon (New York : HarperCollins Children's Books, 2012)
Traces the parallel stories of estranged Irish sisters Sybil and Nula and American orphans Naomi and Lizzie, whose respective explorations into their identities and struggles with misfortune are told in rotating voices.
Keywords: Sisters -- Fiction; Orphans -- Fiction; Identity (Psychology) -- Fiction